2016
DOI: 10.17795/bhs-35842
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice Regarding Physical Activity in Nursing and Midwifery Students

Abstract: Background: There are some mediators that affect physical activity such as knowledge and attitude. Some barriers such as lack of time, bad environments may impede doing physical activities. It sounds that lack of time is a common barrier to do physical activity in nursing and midwifery students. Since they encounter some factors that affect their health, this knowledge, attitude and practice (KAP) study may be helpful to maintain and improve their health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
2
3
3
1
Order By: Relevance
“…This study also assessed the attitudes of BEd students towards physical activity using three point likert scales on seven attitude related statements. A large majority of participants (97.18%) agreed that physical activity help them to stay healthy, which was very close to the findings shown by studies done in Nepal (96.89%), India (97.53%) and Iran (96%) (Sharma S et al, 2023;Alagappan TR et al, 2022;Hosseinzadeh K et al, 2017) but slightly higher than that shown by a study done in South Africa (90.87%) (Mangoejane PK., 2016). The finding on physical activity improving participants' recreational ability as shown by this study (95.07%) was found to be much higher than that shown by another study done in Nepal (79.07%) and almost three-fold higher than that shown by a study done in Iran (32%) (Sharma S et al, 2023;Hosseinzadeh K et al, 2017).…”
Section: Discussionsupporting
confidence: 76%
“…This study also assessed the attitudes of BEd students towards physical activity using three point likert scales on seven attitude related statements. A large majority of participants (97.18%) agreed that physical activity help them to stay healthy, which was very close to the findings shown by studies done in Nepal (96.89%), India (97.53%) and Iran (96%) (Sharma S et al, 2023;Alagappan TR et al, 2022;Hosseinzadeh K et al, 2017) but slightly higher than that shown by a study done in South Africa (90.87%) (Mangoejane PK., 2016). The finding on physical activity improving participants' recreational ability as shown by this study (95.07%) was found to be much higher than that shown by another study done in Nepal (79.07%) and almost three-fold higher than that shown by a study done in Iran (32%) (Sharma S et al, 2023;Hosseinzadeh K et al, 2017).…”
Section: Discussionsupporting
confidence: 76%
“…A survey conducted in Australian universities suggested that 90% of men and 82% of women met the criteria suggested by the physical activity guidelines [ 27 ]. A study on nursing students suggested that some types of physical activity offered in schools and universities might be more attractive to male students than to female ones [ 28 ]. Disparities between sexes in offering services related to BSF in universities should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…A study done in Iran reveals that majority (96%) of the students felt that physical activity makes them healthier and 32% felt the need for physical activity. 8 In a study done in Saudi Arabia also students had good knowledge about physical activity and its role in protection of diseases in general but knowledge regarding protection against specific diseases like diabetes and hypertension dropped to 36% and 28% respectively. 9 These differences may be due to differences in the sample.…”
Section: Discussionmentioning
confidence: 99%